A Study on the Relationship Between the Affordability of Private Residential Property and its Demand in Singapore - Rangaswamy, Easwaramoorthy; Chong, Yen; Nawaz, Nishad (Frontiers in Built Environment, 2022)
Over the years, private housing prices skyrocketed and the high demand to own private housing remained unmet. Prices influenced the perception of affordability and would also affect the demand for private housing. The urgency to understand the intertwined relationships between housing cost (prices), affordability and demand especially in the COVID-19 pandemic situation are high. Hence, this research aimed to quantify the relationship or impact of rising prices on the private housing affordability and its demand. The results from this research could conclude that soaring prices lowered the affordability of buyers and delay the purchase of private property shortly. However, the demand to purchase a private property was higher with rising prices suggesting that higher prices indicate more wealth and potential to own a more valuable asset. Affordability is a temporary barrier to own private properties. This implied that the wealth effect from properties likely outweighed that of the consumption or income substitution effect. This understanding of the relative impacts between housing cost, affordability and demand would contribute significantly to policymaking in providing signals and advice for policymakers to prioritise social mobility or investment return from the property market.